EXAMINING THE IMPACT OF ETHICAL LEADERSHIP ON EMPLOYEES' ETHICAL BEHAVIOR: THE ROLE OF ORGANIZATIONAL JUSTICE AND EMPLOYEES' MORAL IDENTITY - Al Halbusi, Hussam -; Ismail, Mohd Nazari; Omar, Safiah (Journal of Technology Management and Business, 2019)
This paper investigates the role of organizational justice and moral identity of employees on the relationship between ethical leadership and employees' ethical behavior. It examines the mediation effect of organizational justice on the relationship between ethical leadership and ethical behavior of employees. This study also explores the moderating role of employees' moral identity on the relationship between organizational justice and ethical behavior of employees. Data is obtained from a sample of 230 employees from the banking industry in Iraq. The theoretical and practical contribution as well as recommendations for further research are also presented.